PENGARUH JENlS PELARUT ORGANIK DAN UMUR DAUN PINUS TERHADAP RENDEMEN LILIN - Bambang Wiyono (Pusat Penelitian dan Pengembangan Hasil Hutan, 1995)
The objective of this research is to study the effect of organic solvents and pine needles age on wax yields. The organic solvents used in extracting wax consisted of chloroform, n hexane and ethanol; however, the radiate pine needles' age used as raw materials for the action were primary pine needles (one year old or less), secondary pine needles (two o tu, e years old), and mixtare of both. the data were analysed with an A x B factorial design where A represented organic solvents and B depicted pine needles' age. the differenc between means of wax yields was calculated with an LSD method in the SAS compute packages.Results showed that organic solvents, pine needles' age and the interaction of both gave ,high fr significance on wax yields. Compared lo the other combinations, a combination of. chtorofonn solvent and secondary pine needles produced the highest of wax yield. A wax yiet. obtained by extracting secondary pine needles was statistically similar lo a wax yield obtaine, frotn a mixture of both primary and secondary pine needles. A chloroform solvent is a goo. solvent to extract pine needle waxes from any kind of pine species.